Prevalence of Complementary and Alternative Medicine Use in the General Population in the Czech Republic - Pokladnikova, Jitka; Selke-Krulichova, Iva (Forschende Komplementarmedizin (2006), 2016)
BACKGROUND: Prevalence rates of complementary and alternative medicine (CAM) use are still missing for some European countries, especially in the East. Thus, we measured patterns and determinants of CAM use among a representative sample of the general population in the Czech Republic. METHODS: A cross-sectional survey was conducted. A sex-, age- and region-stratified sample of citizens aged 15 and older were randomly selected from voter registration lists (n = 8,639,375). RESULTS: Overall, 76.0% (n = 1,365) of the respondents reported use of one or more CAM modalities during the past 30 days. The top five CAM modalities used were vitamins/minerals (54.6%), herbal remedies (47.8%), massage (19.9%), relaxation techniques (9.5%), and dietary supplements excluding vitamins/minerals (9.2%). Prevention (82.0%) was the primary reason for CAM use. Only 15.9% of CAM users employed it for therapeutic purposes. The most commonly treated ailments were respiratory (35.0%) and musculoskeletal (33.6%) disorders. CONCLUSION: The prevalence of CAM use in the Czech Republic is high, especially among people who apply CAM for self-treatment prior to seeing a doctor. Half of the study population combined CAM with conventional medical treatment, which may result in potential harm to the patient. Healthcare providers as well as the public should be educated about effective and safe use of CAM.
Keywords: Adolescent; Adult; senioři; Aged; Male; lidé; lidé středního věku; Humans; Middle Aged; Young Adult; Czech Republic; senioři nad 80 let; Aged, 80 and over; průřezové studie; mužské pohlaví; dospělí; Complementary Therapies; komplementární terapie; mladý dospělý; Cross-Sectional Studies; Česká republika; ženské pohlaví; mladiství; Female